Prevalence of subclinical mastitis in different breeds of goats - Shalini, Vaswani (Veterinary Practitioner, 2014)
Subclinical mastitis(SCM) deteriorates both quantity and quality of milk. Subclinical mastitis is 15 to 40 times more prevalent than its clinical form in goats.The present study was carried out to assess the status of SCM in different breeds of goats, the involvement of bacterial agents and their sensitivity to antibiotics.In our study, the overall prevalence rate of subclinical mastitis among the goats was determined 24.2% which is in accordance with the earlier reports. Jakhrana breed showed highest prevalence of SCM (36.36%) followed by Barbari (28.18 %) and Jamunapari (8.18 %).The variability in prevalence among the breeds may be attributed to the difference in management practices of the farms, technical knowledge of the investigators, genetic resistance and tests/methods used for the diagnosis of SCM.CNS were found as the most frequently isolated bacteria from subclinical goat mastitis, whereas the second most common cause after the CNS was Bacillus sp. Previous studies support the findings of our study. Antibiotic resistance was not observed among the targeted bacterial isolates in antimicrobial sensitivity test which may be attributed to proper and judicious use of antibiotics as per the standard recommendations
Only IISERM authors are available in the record.
Keywords: Mastitis; Goat; Staphylococcus; Subclinical